Net Irrigation Requirements for Florida Turfgrass Lawns: Part 3 - Theoretical Irrigation Requirements - Consuelo C. Romero; Michael D. Dukes (EDIS, 2011)
Urban water users need specific recommendations to irrigate efficiently and for planning and regulatory programs. This 21-page fact sheet estimates net irrigation, effective rainfall, and drainage by using a water balance equation for ten locations in Florida and one in Alabama from data during the 30-year period of 1980-2009. Written by Consuelo C. Romero and Michael D. Dukes and published by the UF Department of Agricultural and Biological Engineering, August 2011. (UF/IFAS Photo: Josh Wickham)